2021
DOI: 10.1021/acs.langmuir.1c01525
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Reorientation During Deposition Onto Metal Surfaces of Quasi-Two-Dimensional Langmuir Monolayers Composed of Bifunctional Amphiphilic, Twisted Perylenes

Abstract: Supramolecular dye structures, which are often ruled by π−π interactions between planar chromophores, crucially determine the optoelectronic properties of layers and interfaces. Here, we present the interfacial assembly of perylene monoanhydride and monoimide that do not feature a planar chromophore but contain chlorine substituents in the bay positions to yield twisted chromophores and hence modified π-stacking. The assembly of the twisted perylene monoanhydride and monoimide is driven by their amphiphilicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…For Π LB = 12 mN/m, where the excess area starts rising, phase-separated domains similar to the 10:SA system are observed, hence showing phase separation. Consequently, although the c ( 10 ) TPCA = 80% Langmuir layer featured the most negative excess area (Figure ) as compared to other blending ratios and as compared to SA matrices (Figure ), TPCA tends to show two-dimensional crystallites, possibly formed during the deposition process . According to our findings for the SA blends discussed above, the spherical features of the opposing phase (blue in Figure B) as compared to the surroundings are assigned to dye 10 .…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…For Π LB = 12 mN/m, where the excess area starts rising, phase-separated domains similar to the 10:SA system are observed, hence showing phase separation. Consequently, although the c ( 10 ) TPCA = 80% Langmuir layer featured the most negative excess area (Figure ) as compared to other blending ratios and as compared to SA matrices (Figure ), TPCA tends to show two-dimensional crystallites, possibly formed during the deposition process . According to our findings for the SA blends discussed above, the spherical features of the opposing phase (blue in Figure B) as compared to the surroundings are assigned to dye 10 .…”
Section: Resultsmentioning
confidence: 59%
“…Such phase separations are not obvious from the excess areas for low dye concentrations or for the TPCA matrix. Therefore, we conclude that the deposition process influences phase separation . Using PiFM to assign the segregated domains to the matrix or dye, we also found that phase separation of identically composed Langmuir monolayers deposited at high surface pressures (Π LB > 8 mN/m) differs between deposition onto glass and onto gold, thus highlighting the influence of the substrate on phase separation kinetics.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The highest rigidity of the MPEGC 60 Langmuir layer at mma C (C −1 S,max ) = 68 Å 2 corresponds to the inflection point in the Π(mma) isotherm being referred to as the collapse point of the monolayer. [ 17 ] Consequently, the Langmuir technique provides a tool to systematically tune the mma from loose to dense and rigid packing at the collapse point of the monolayer.…”
Section: Resultsmentioning
confidence: 99%
“…The Langmuir layers are deposited using the LB technique at different packing densities, specifically at areas A LB = 35, 32, 31, 29, 28 Å 2 , corresponding to Π LB = 5, 10, 15, 20, 25 mN/m, as indicated by the dotted lines in Figure 1. Exemplarily, Figure 2A shows atomic force microscopy images of an imperfect layer section [45] to determine the resulting film thickness (B and C) for a LB monolayer deposited at Π LB = 25 mN/m (see Figure S2 in the Supporting Information for larger areas of a perfect LB layers). Figure 2C shows the height distribution of the region shown in panel A.…”
Section: Surface Pressure-area Isotherms and Lb Layersmentioning
confidence: 99%